(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The viral disease known as inclusion body hepatitis (IBH) spreads rapidly among chicken flocks.This disease had been described in Iraq, since 1970s. However, in the recent few years, the severity and mortality of the disease have been dramatically increased in our region. In this article, we sought to describe and detect the causative agent serotype depending on molecular bases. For further confirmation, histological methods have also been used for better understanding.For this purpose, young broiler (18 – 22 day old) with acute IBH infection collected from four distinct geographical regions have been subject to the study. Livers were taken under sterile conditions for histopathological study. Hematoxylin and eosin (H & S) stains were used to examine liver tissue that had been sectioned at 5 microns and embedded in paraffin blocks for microscopic examination. Our findings suggest that the serotype of the IBH in Iraq is fowl adenoviruses (FAdVs). The samples showed severe reactions where acute hepatitis is prominent with hepatic necrosis and massive basophilic and eosinophilic intranuclear inclusion bodies. Other, non-specific histopathological changes have also been reported such as infiltration of inflammatory cells, hemorrhages and edema